Adenovirus-vectored Ebola vaccines. (3rd October 2015) - Gilbert, Sarah C
Abstract : The 2014 outbreak of Ebola virus disease in West Africa has highlighted the need for the availability of effective vaccines against outbreak pathogens that are suitable for use in frontline workers who risk their own health in the course of caring for those with the disease, and also for members of the community in the affected area. Along with effective contact tracing and quarantine, use of a vaccine as soon as an outbreak is identified could greatly facilitate rapid control and prevent the outbreak from spreading. This review describes the progress that has been made in producing and testing adenovirus-based Ebola vaccines in both pre-clinical and clinical studies, and considers the likely future use of these vaccines.